Screening for toxoplasmosis in pregnancy. Issue 6 (June 1981) - Broadbent, E J; Ross, R; Hurley, R
Abstract : The prevalence of antibody against Toxoplasma gondi in a population of 715 pregnant women has been evaluated by two methods: indirect haemagglutination antibody (IHA) and indirect fluorescent antibody (IFA) test and all positive sera were checked by the dye test. Five hundred of the study population were questioned on diet and on animal contact to elucidate a possible relation to the prevalence of antibody. Results are expressed in international units (IU) of antibody against T gondi. Of the 715 sera, 171 were positive by IHA and 173 by IFA. One hundred and sixty-seven sera were positive by both tests, ninety-eight (58%) correlating exactly, as to the concentration of antibody. The ten sera which were not positive by both tests all had detectable antibody at the minimum concentration only (12 IU). The dye test confirmed all sera positive by both tests with the exception of three. It also confirmed one of four sera positive by IHA antibody alone and two of six positive by IFA alone. All sera that proved dye test-negative had low antibody concentrations (12 IU) by IHA or IFA. The IHA test, which is commercially available in kit form, would be suitable for use as a screening test during pregnancy. The estimated annual rate of antibody acquisition over the age range 16-40 years is 1.2% per annum with the highest rate in the 36-40 age group (2.5% per annum) and the lowest in the 26-30 age group (0.4% per annum). The clinical history was not significantly different between those with and those without antibody against T gondi but significantly more women in the 36-40 age group had a history of animal contact than those in the 26-30 age group. No conclusive evidence of recent or current infection was found.